(untitled) (Bulletin of Innovative Research, 2026)
the article examines the conflict between theory and real life in I. S. Turgenev’s novel Fathers and Sons. It analyzes the character of Yevgeny Bazarov as a representative of nihilistic theory and traces the transformation of his views under the influence of real-life circumstances. Special attention is paid to the generational conflict, the theme of love, and the internal contradictions of the protagonist. The study is based on literary and interpretative analysis methods. It concludes that Turgenev demonstrates the limitations of abstract theories that ignore the complexity of human nature.